OSCDMA Double Weight Code: a simplified formula code construction technique - Mohammed, A.; Babekir, E.I.; Elfadel, N.; Saad, N.M.; Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org